Proportion of stroke types in Madagascar: a tertiary-level hospital-based case series - Riedmann, Julia; Solonavalona, Andriamihaja Flavien; Rakotozafy, Adriamboahanginiaina Ravosoa; Ralamboson, Solofo; Endres, Matthias; Siegerink, Bob; Siebert, Eberhard; Knauss, Samuel; Emmrich, Julius (PLOS ONE, 2022)
Background Like other countries in sub-Saharan Africa, Madagascar has a high burden of stroke. The Malagasy population is unique in sharing both African and Asian ancestry. The proportion of ischemic and hemorrhagic stroke types is unknown for this population. Aim Our aim was to establish the proportion of stroke types and known risk factors for the Malagasy population. Methods We conducted a single-center, tertiary-level hospital-based case series. We included all patients with a CT-imaging confirmed stroke who presented at the emergency ward of the study hospital between January 1, 2017, and November 20, 2018. Results Of 223 patients with CT-confirmed stroke, 57.4% (128/223, 95% CI: 51-64%) had an ischemic stroke and 42.6% (95/223, 95% CI: 36-49%) had an intracranial hemorrhage. The majority (89.5%; 85/95, 95% CI: 83-96%) of intracranial hemorrhages were intracerebral; 4.2% (4/95, 95% CI: 0-8%) had a subdural hematoma, 5.3% (5/95, 95% CI: 1-10%) had a subarachnoid hemorrhage, there was one isolated intraventricular hemorrhage (1.1%; 1/95, 95% CI: -1-3%). The prevalence of hypertension among stroke patients was high (86.6%; 187/216, 95% CI: 82-91%). Conclusions Our study is the first to report the proportion of stroke types and known risk factors in Madagascar. We find that the proportion of hemorrhagic strokes was unexpectedly higher than that reported from other countries in sub-Saharan Africa. Our findings highlight the need for a country-specific approach to stroke prevention, treatment, and rehabilitation and provide guidance on public health resource allocation in Madagascar.
Gesehen am 03.05.2023